Ventilación mecánica en pacientes con membrana hialina - Rocafuerte Gaibor, Wellington Guillermo (2019)
This work offers statistical data, results, results, results, results, problems of prematurity and diseases of the membrane, the syndrome of respiratory distress and the behavior of the ability to respond to this disease. The prematurity rates of maintenance below 3.0% and the incidence of the disease of the membrane is less than 0.3%. Survival after this disease shows an upward curve.